2018
DOI: 10.1542/peds.2017-0213
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Immunodeficiency: A New Association With Early-Onset Childhood Panniculitis

Abstract: We report on 4 children who presented with aseptic panniculitis associated with inherited immunodeficiency. Three patients had a B-cell immunodeficiency resulting from mutations in the TRNT1 and NF-κb2 genes (no mutation was found in the third patient), and 1 had a T-cell deficiency (mutation in the LCK gene). Panniculitis occurred before the age of 2 years in the 4 patients and preceded the onset of recurrent infections because of immunodeficiency in 2. It presented either as nodules, which resolved spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…Bader-Meunier et al reported four cases of early-onset panniculitis associated with inherited B-or T cell immunodeficiency [43]. Of the four cases reported, compound heterozygous mutation in TRNT1 (c.1213G>A/c.1057-7C>G) was identified in one child, expanding the repertoire of phenotypes associated with TRNT1.…”
Section: Trnt1 and Diseasementioning
confidence: 96%
“…Bader-Meunier et al reported four cases of early-onset panniculitis associated with inherited B-or T cell immunodeficiency [43]. Of the four cases reported, compound heterozygous mutation in TRNT1 (c.1213G>A/c.1057-7C>G) was identified in one child, expanding the repertoire of phenotypes associated with TRNT1.…”
Section: Trnt1 and Diseasementioning
confidence: 96%
“…However, one adult patient presented lichen sclerosus et atrophicus and morphea (6). Panniculitis, but not relapsing erythema nodosum, was previously reported in one SIFD patient (7). Since the first publication on SIFD, several studies have described other patients harboring disease-causing mutations in TRNT1, notably bearing phenotypes incompatible with the original description, such as the present case.…”
Section: Discussionmentioning
confidence: 45%
“…There are few reports of NP in the pediatric age group, including one patient with rheumatoid arthritis, one on granulocyte colony‐stimulating factor, and few receiving vemurafenib . It has recently been also reported in children with PI including TRNT1 , NF‐ normalκ b2 , and LCK gene mutations …”
Section: Discussionmentioning
confidence: 99%